THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON PROSOCIAL BEHAVIOR AMONG SENIOR HIGH SCHOOL STUDENTS: THE MODERATING ROLE OF GENDER - Wijayanti, Wahyuningsih Kusuma; Mahfud, Ashari (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Prosocial behavior refers to voluntary actions intended to help others without expecting rewards, and it is considered an essential component in the development of adolescents' social character. This study aims to examine the influence of emotional intelligence on prosocial behavior among senior high school students in Semarang City, while also analyzing the moderating role of gender in this relationship. Employing a quantitative approach, this research involved 200 students selected through purposive sampling. The instruments used were an emotional intelligence scale (? = 0.875) and a prosocial behavior scale (? = 0.861), developed based on Goleman’s and Mussen’s theoretical frameworks. Data were analyzed using Moderated Regression Analysis (MRA). The results showed that emotional intelligence had a positive and significant influence on students’ prosocial behavior (? = 0.624, p < 0.001). Furthermore, gender was found to moderate the relationship (R² change = 0.043, p < 0.05), indicating that the influence of emotional intelligence on prosocial behavior was stronger among female students compared to their male counterparts. These findings offer important implications for the development of character education and school counseling programs, particularly those based on emotional intelligence and gender-responsive approaches.